Lactobacillus plantarum bacteriophages isolated from Kefir grains: phenotypic and molecular characterization - de Antoni, Graciela (2010)
Two greatly related Lactobacillus plantarum bacteriophages (named FAGK1 and FAGK2) were isolated from Kefir grains of different origins. Both phages belonged to the Siphoviridae family (morphotype B1) and showed similar dimensions for head and tail sizes. The host range of the two phages, using 36 strains as potential host strains, differed only in the phage reactivity against one of them. The phages showed latent periods of 30 min, burst periods of 80 ± 10 min and burst size values of 11.0 ± 1.0 PFU per infected cell as mean value. Identical DNA restriction patterns were obtained for both phages with PvuI, SalI, HindIII and MluI. The viral DNA apparently did not present extremes cos and the structural protein patterns presented four major bands (32.9, 35.7, 43.0 and 66.2 kDa).             This study reports the first isolation of bacteriophages of Lb. plantarum from Kefir grains and adds further knowledge regarding the complex microbial community of this fermented milk.